A study of the problem of loneliness in the times of war - Skwarek, Beata; Lozynska, Iryna (Studium problemu samotności w czasach wojny, 2023)
The article summarizes a view on the problem of loneliness faced by displaced persons and refugees on the European continent in the past century. The emergence of refugees was caused by military conflicts of various origins, from the two world wars to a number of local armed confrontations. The contemporary reality poses serious challenges in this respect: the war launched by Russia against Ukraine has caused another wave of refugees and displaced persons. Since the beginning of the war, the authorities of the European Union have been facing a “migration crisis”. The historical retrospective of the phenomenon presented in the article shows that the problem is global and difficult to solve.
Zeszyty Naukowe Collegium Witelona, nr 49(4)/2023, s. 71-80
Keywords: refugees; internally displaced persons; Europe; war; loneliness; migration crisis; uchodźcy; osoby wewnętrznie przesiedlone; Europa; wojna; samotność; kryzys migracyjny